-30x+9+30x-30=x-7
-21=x-7
adding 7
x=-14
2006-12-10 17:02:58
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
–3(10x – 3) + 10(3x – 3) = x – 7
-30x+9+30x-30=x-7
-21=x-7
x= -14
hope its fine..
2006-12-11 06:13:15
·
answer #2
·
answered by For peace 3
·
0⤊
0⤋
-3(10x - 3) + 10(3x - 3) = x - 7
-30x + 9 + 30x - 30 = x - 7
-30x + 30x -x = -7 + 30 - 9
-x = 14
x = -14
to check:
LHS = -3[(10*-14) - 3] + 10[(3*-14) - 3]
= -3(-140-3) + 10(-42-3)
= -3(-143) + 10(-45)
= 429 -450
= -21...............(1)
RHS = -14 -7
= -21...............(2)
from (1) &(2)
LHS=RHS
hence, x = -14
2006-12-11 01:44:39
·
answer #3
·
answered by aadhyagupta 2
·
0⤊
0⤋
jus multiply the whole as shown below and find the answer..
-3(10x-3)+10(3x-3)=x-7
(-30x)+(9)+(30x)-(30) = x -7
-21+7= x
x= -14....
2006-12-11 01:19:28
·
answer #4
·
answered by latha 2
·
0⤊
0⤋
By expanding the 1st and 2nd bracket :
-30x + 9 +30x -30 = x-7
after combining Like terms and this stuff :
-21 = x-7
x = -21+7
x = -14
2006-12-11 01:15:06
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
-30x + 9 + 30x - 30 = x - 7
-21=x - 7
x = -14
2006-12-11 01:10:16
·
answer #6
·
answered by Dee 2
·
0⤊
0⤋
-3(10x-3)+10(3x-3)=x-7
-30x+930x-30=x-7
9-30=x-7
-21=x-7
-21+7=x
x=-14
the answer is -14.
2006-12-11 10:25:38
·
answer #7
·
answered by tarena 2
·
0⤊
0⤋
-30x+9+30x-30=x-7
9+7-30=x
x=-14
2006-12-11 01:52:07
·
answer #8
·
answered by fakhrbijan 1
·
0⤊
0⤋
-14
2006-12-11 01:05:09
·
answer #9
·
answered by spaabroadway 3
·
0⤊
0⤋
do your own homework. lazy kids.
2006-12-11 01:00:22
·
answer #10
·
answered by IMHO 6
·
2⤊
1⤋